MASIH PERLUKAH SASTRA DI ERA INDUSTRI ? - Eriyanti, Ribut Wahyu (Jurnal Bestari, 1992)
Learning literature will remind us on the process of Indonesia's physical revolution. Reading through Chairil Anwar's poem entitled